2016
DOI: 10.1080/23744731.2017.1251265
|View full text |Cite
|
Sign up to set email alerts
|

Experimental study of the flow characteristics in a falling film liquid desiccant dehumidifier

Abstract: The flow characteristics play great role in determining the heat and mass transfer performance of a falling film liquid desiccant dehumidifier. Even though there have been lots of studies reporting the flow behaviors in different devices and fields, the fundamental researches of the film flow characteristics in a liquid desiccant dehumidifier were still very limited, especially for experiment. Therefore, in present work, a simple single channel test rig was established for observing and describing the flow cha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 24 publications
0
5
0
Order By: Relevance
“…Therefore, a correlation for the liquid oxygen under the range of Ka = 3532–6558 is fitted as shown in Equation . The exponent 0.904 of Ka is similar to 0.975 10 but bigger than 0.6 7–9,12 or 0.764 11 . It shows that Ka has a greater impact on the wettability of liquid oxygen, which is different from that of water.…”
Section: Resultsmentioning
confidence: 84%
See 3 more Smart Citations
“…Therefore, a correlation for the liquid oxygen under the range of Ka = 3532–6558 is fitted as shown in Equation . The exponent 0.904 of Ka is similar to 0.975 10 but bigger than 0.6 7–9,12 or 0.764 11 . It shows that Ka has a greater impact on the wettability of liquid oxygen, which is different from that of water.…”
Section: Resultsmentioning
confidence: 84%
“…Analogous to the first formula, the empirical correlation was put forward for the film flow of LiCl solution on the vertical plate. The discrepancies between the predictions and experimental data are within ±2% 12 . As seen, both the Kapitza number Ka and contact angle θ have a great impact on Re c .…”
Section: Introductionmentioning
confidence: 68%
See 2 more Smart Citations
“…For the vertical film flow, it is found that the film regime is laminar at Re ≤ 1600 [30]. Moreover, the film surface is smooth and laminar near the region of liquid inlet, which is defined as the wave inception [31,32]. Furthermore, we acquired the length of wave inception at Re = 1600, for the water was less than 20 cm (see Figure 3 in [32]).…”
Section: Assumptions and Mathematical Modelsmentioning
confidence: 99%